2014
DOI: 10.7554/elife.01489
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis for the prion-like MAVS filaments in antiviral innate immunity

Abstract: Mitochondrial antiviral signaling (MAVS) protein is required for innate immune responses against RNA viruses. In virus-infected cells MAVS forms prion-like aggregates to activate antiviral signaling cascades, but the underlying structural mechanism is unknown. Here we report cryo-electron microscopic structures of the helical filaments formed by both the N-terminal caspase activation and recruitment domain (CARD) of MAVS and a truncated MAVS lacking part of the proline-rich region and the C-terminal transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 67 publications
7
117
2
Order By: Relevance
“…Higher‐order complexes, that is, oligomers in which the number of monomers in a complex is broadly distributed and can be large, have important functions in signal transduction and cell fate decisions (Credle et al , 2005; Korennykh et al , 2009; Yin et al , 2009; Li et al , 2012a; Banjade & Rosen, 2014; Lu et al , 2014; Xu et al , 2014). The inherent size heterogeneity of such higher‐order assemblies generates challenges for their structural and mechanistic characterization, but recent progress has provided insight into their ability to mediate signal amplification, filter noise, and regulate signaling in time and space (Li et al , 2012b; Wu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Higher‐order complexes, that is, oligomers in which the number of monomers in a complex is broadly distributed and can be large, have important functions in signal transduction and cell fate decisions (Credle et al , 2005; Korennykh et al , 2009; Yin et al , 2009; Li et al , 2012a; Banjade & Rosen, 2014; Lu et al , 2014; Xu et al , 2014). The inherent size heterogeneity of such higher‐order assemblies generates challenges for their structural and mechanistic characterization, but recent progress has provided insight into their ability to mediate signal amplification, filter noise, and regulate signaling in time and space (Li et al , 2012b; Wu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While the molecular mechanism regarding CYLD downregulation remained mostly elusive, our results indicated that miR-526a modulates CYLD expression and affects cell apoptosis via CYLD. Therefore, our findings may have implications for the involvement of miR-526a in the development and progression of other carcinomas linked to loss of CYLD [31]. In summary, we have shown that miR-526a directly stimulate cancer progression through its effect on cancer cell proliferation, indicating its potential role as an oncogene.…”
Section: Discussionmentioning
confidence: 81%
“…This activated complex of RIG-I is then able to interact with its adapter MAVS [90], also known as IPS-1, Cardif and VISA [91][92][93], promoting aggregation of MAVS [94], and redistribution of MAVS and mitochondria [95]. This unique tetrameric structure of RIG-I possibly promotes the formation of a seed fiber of MAVS, which then results in the three-stranded prion-like fibers in cells that robustly activate downstream signaling [96][97][98]. The exact mechanism for the formation of a seed fiber of MAVS and how different RIG-I-RNA complexes activate MAVS remains unknown.…”
Section: Mechanism Of Activation Of Rig-imentioning
confidence: 96%